2017
DOI: 10.1038/s41598-017-15915-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism related to monocyte-macrophage function is associated with graft-versus-host disease

Abstract: Despite detailed human leukocyte antigen (HLA) matching and modern immunosuppressive therapy, severe graft-versus-host disease (GvHD) remains a major hurdle for successful allogeneic hematopoietic stem cell transplantation (HSCT). As the genetic diversity in GvHD complicates the systematic discovery of associated variants across populations, we studied 122 GvHD-associated single nucleotide polymorphisms (SNPs) in 492 HLA-matched sibling HSCT donor-recipient pairs from Finland and Spain. The association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
1
20
0
3
Order By: Relevance
“…We discovered pathways associated with aGvHD pathogenesis, implicating immunological responses in processes such as T cell function, cytokines, JAK-STAT signaling, and regulation of the TRAF6 gene. The risk for GvHD has mainly been investigated during past decades by concentrating on the MHC region and specific candidate genes (10,11), and only in recent years has the use of genome-wide approaches emerged in the field (16,17,(19)(20)(21)(22). These studies have shown the importance of genetic component in HSCT complications, but the results remain diverse, and their replication is incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We discovered pathways associated with aGvHD pathogenesis, implicating immunological responses in processes such as T cell function, cytokines, JAK-STAT signaling, and regulation of the TRAF6 gene. The risk for GvHD has mainly been investigated during past decades by concentrating on the MHC region and specific candidate genes (10,11), and only in recent years has the use of genome-wide approaches emerged in the field (16,17,(19)(20)(21)(22). These studies have shown the importance of genetic component in HSCT complications, but the results remain diverse, and their replication is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Finnish Cohort 1 and Spanish Cohort 1 have been described previously in detail (11). Briefly, Finnish Cohort 1 consisted of 239 donor-recipient pairs, 23 individual recipients, and 28 individual donors with available clinical data and imputed genotype.…”
Section: Study Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA samples from the Finnish cohort were extracted using the QIAamp DNA Blood Mini Kit (Qiagen, Germany). Imputation was carried out as in 17 according to instructions of 18 using plink 1.90b3.29 19 for quality filtering and IMPUTE2 20 for the actual imputation with 1000 Genomes Phase 3 21 as a phased reference. Post-imputation filtering excluded variants having an IMPUTE2 INFO-field <0.5.…”
Section: Genotypingmentioning
confidence: 99%